2011
DOI: 10.1177/0954407011411638
|View full text |Cite
|
Sign up to set email alerts
|

Crashworthiness design optimization using equivalent static loads

Abstract: Crashworthiness is an issue that should be considered when designing a passenger vehicle to ensure the occupants' safety in a vehicle accident. Many governments and insurance companies around the world suggest conditions relating to passenger safety in designing vehicles, and regulations that include the conditions have been utilized. The suggested regulations reflect the crashworthiness of structures in order to consider passenger safety. Therefore, these conditions should be used as objective functions or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Many studies using ESLM have been reported with regard to practical crash optimization problems. 4,15,16,19,20,30…”
Section: Crash Optimization Methodsmentioning
confidence: 99%
“…Many studies using ESLM have been reported with regard to practical crash optimization problems. 4,15,16,19,20,30…”
Section: Crash Optimization Methodsmentioning
confidence: 99%
“…It is noted that the relationship of responses from different load cases can be considered as an objective function or a constraint in linear static-response structural optimization. 22…”
Section: Eslm Considering Hicmentioning
confidence: 99%
“…Among them, HIC is the factor that has the greatest influence on the survival rate. 22 In this study, crash optimizations are performed by considering the HIC as an objective function or a constraint. In 1972, NHTSA defined HIC to indicate the severity of head injuries as follows…”
Section: Eslm Considering Hicmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The ELSM was proposed to overcome these problems, and it has been applied to large and practical examples. 511 This method has an analysis domain and a design domain. 12 Non-linear dynamic analysis is performed in the analysis domain, equivalent static loads (ESLs) are generated and gradient-based linear static structural optimization is carried out with the ESLs in the design domain.…”
Section: Introductionmentioning
confidence: 99%